Use of Technology in Disaster Management - Bhandari, Vijan (Unity Journal, 2022)
Natural disasters are uncontrollable and cannot be avoided, although their effects can be mitigated in many ways, but human-caused catastrophes can be avoided and limited if people become more aware of their actions. Frequent occurrences of disasters have caused many casualties, destroyed physical properties, and created environmental damage which is raising concern in Nepal and the world as a whole. This study focuses at analyzing several technologies mainly on Robotics, Drone Technology, Mobile Phone and Social Medias, Internet of Technology and Artificial Intelligence that have been used and can be used for disaster management. These technologies are used in the three phases of disaster management, primarily the pre-disaster phase, disaster phase, and post-disaster phase, are explored to see how they can be used for predicting upcoming disasters, acting quickly and effectively during disasters, and analyzing the impact of disaster damage caused by disasters. This article would also be helpful to know about the development in technologies that have been achieved and further development that can be done to minimize the effect and casualties caused by disasters and also implement them in the necessary areas possible in our country as it is highly prone to the frequent occurrence of natural calamities.